Criminal Policy of Ukraine through EU Dimensions - Туляков, Вячеслав Олексійович; Туляков, В. О.; Туляков, Вячеслав Алексеевич; Tulyakov, Vyacheslav A.; Tuliakov, Viacheslav O. (Братислава : Academic Publishing House Researcher s.r.o., 2015)
The article deals with the aspects of the current criminal legislation of Ukraine. The author outlines a new Theoretical Model of the Criminal Code of Ukraine. The main attention is given to the approximation of Ukrainian legislation to the European norms and standards.

У статті розглядаються аспекти чинного кримінального законодавства України. Автор окреслює нову теоретичну модель Кримінального кодексу України. Основна увага приділяється наближенню українського законодавства до європейських норм та стандартів.

В статье рассматриваются аспекты действующего уголовного законодательства Украины. Автор излагает новую теоретическую модель Уголовного кодекса Украины. Основное внимание уделяется приближению украинского законодательства к европейским нормам и стандартам.
Tulyakov V. A. Criminal Policy of Ukraine through EU Dimensions / V. A. Tulyakov // Журнал гражданского и уголовного права. - 2015. - Т 3. - Вып. 1. - С. 23-26.
Keywords: EU; criminal policy of Ukraine; a new Theoretical Model of the Criminal Code of Ukraine; criminal liability; ЄС; кримінальна політика України; нова теоретична модель Кримінального кодексу України; кримінальна відповідальність; ЕС; уголовная политика Украины; новая теоретическая модель Уголовного кодекса Украины; уголовная ответственность; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law